Integrating Islamic Economics and Climate Finance: A Global Bibliometric Mapping - Muhamad Dupi; Inayat Ullah Baloch Baloch (Jurnal Magister Ekonomi Syariah, 2025)
The escalating concern of climate change has heightened academic focus on institutions of sustainable financing and the role of Islamic financing and finance. Although Islamic social finance, green sukuk, and sustainability have been previously discussed in terms of normative or case-based approaches, a systematic worldwide mapping of the research patterns that combine the Islamic economics perspective with climate finance has not been done in a systematic way. This paper tries to fill this gap by doing a bibliometric review of 126 journal articles located in the Scopus database and published between 2014 and 2025, and additional data is gathered on 25 September 2025. Based on bibliometric indicators and network visualization with VOSviewer, this study focuses on the analysis of trends in publications, partnerships between countries and institutions, journals and authors with the greatest impact, and the co-occurrence of significant research themes. Based on the results, it is possible to note that the number of publications has significantly risen since 2020, which suggests a growing academic interest in the field of Islamic economics in the context of climate finance. The influential states are Malaysia and Indonesia, which does not only imply high academic ability but also the impact of the proactive national policy, regulating frameworks, and institutional support of integrating Islamic finance and green finance. Keyword analysis also demonstrates the centrality of the terms "Islamic finance," "sustainable finance," and "green sukuk" with the emergence of new terms related to fintech, ESG and decentralized finance, as well as the transition to digital and innovative sustainability-focused financial instruments.